A Most az Apokalipszis? - Boros , János (Kultúratudományi Szemle, 2022)
The Now is the Apokalypse? János Boros The Now is the Apokalypse? is the title of the short paper. Following Malte Henk’s article in Die Zeit, I present and analyze his optimistic thesis that Apocalypse is finally a good thing for humankind since it inducated an attitude in Western culture, which lead to the development of humanities, of science and technology.